2021
DOI: 10.21776/ub.jam.2021.019.02.05
|View full text |Cite
|
Sign up to set email alerts
|

Turnover Intention Among Lecturers in Private Higher Education: The Direct Impact of Financial Rewards and Mediation of Job Satisfaction and Effective Organizational Commitment

Abstract: Lecturer responsibilities in presenting learning materials and building students’ character is considered very important in preparing future workers/entrepreneur. However, those responsibilities still have not received proper attention in certain institutions and even from the government. If this goes on continuously, it is feared that they will lose wellperformed individuals. This study aimed to investigate the level of turnover intention from the lecturer in six private universities in Bandung. And the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
(70 reference statements)
1
3
0
1
Order By: Relevance
“…In table 3 it can be seen that the results of H1 have a P value of 0,000 where this value is smaller than 0,005 so that H1 can be valid in this study. This study has similar results with previous studies from research (Kristanti et al, 2021) and (Lee et al, 2017). Heimerl et al (2020) conducted research on workers in the hotel sector in mountainous areas in western countries, in this study it showed that salary was in the last rank in influencing job satisfaction.…”
Section: Hypothesis Isupporting
confidence: 93%
“…In table 3 it can be seen that the results of H1 have a P value of 0,000 where this value is smaller than 0,005 so that H1 can be valid in this study. This study has similar results with previous studies from research (Kristanti et al, 2021) and (Lee et al, 2017). Heimerl et al (2020) conducted research on workers in the hotel sector in mountainous areas in western countries, in this study it showed that salary was in the last rank in influencing job satisfaction.…”
Section: Hypothesis Isupporting
confidence: 93%
“…Several previous studies found that the turnover rate of lecturers in Indonesia is quite high (Harini et al. , 2020; Kristanti et al. , 2021; Rubiono and Finahari, 2017), reported that lecturers' turnover rate at private higher education institutions in one province in Indonesia, reached 62%.…”
Section: Introductionmentioning
confidence: 94%
“…Several previous studies found that the turnover rate of lecturers in Indonesia is quite high (Harini et al, 2020;Kristanti et al, 2021;Rubiono and Finahari, 2017), reported that lecturers' turnover rate at private higher education institutions in one province in Indonesia, reached 62%. So, it is important to examine the turnover intention at higher education institutions (Rita and Widodo, 2021;Sudarti et al, 2021;Narimawati, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…The work environment shows the work atmosphere of the chosen profession (Kristanti et al, 2021). The working atmosphere includes the nature of work (routine, attractive, overtime), the level of competition among employees, and the pressure of the workload given.…”
Section: Work Environment Influences Career Selectionmentioning
confidence: 99%